Higher Education in Western Balkans: Recent Trends and Challenges - Brajkovic, Lucia (International Higher Education, 2016)
Due to the lack of systematic data collection on national and institutional levels, the higher education systems in the Western Balkans have remained under-researched. This article aims to describe and analyze some of the most salient challenges facing academic sectors in these countries, such as structural issues, growth of the private sector, and EU funding.